Remote sensing of mineral dust over land with MSG infrared channels: A new Bitemporal Mineral Dust Index - Klüser, Lars; Schepanski, Kerstin (Remote Sensing of Environment, 2009)
A new Bitemporal Mineral Dust Index (BMDI) is derived from Meteosat Second Generation (MSG) infrared observations over land at two different time slots per day. This daily dust index is evaluated with AErosol RObotic NETwork (AERONET) surface observations, MODerate resolution Imaging Spectro-radiometer (MODIS) “Deep Blue” Aerosol Optical Depth (AOD) and Ozone Monitoring Instrument (OMI) Aerosol Index, showing a good capability of the BMDI for dust detection and dust load estimation over land and also over deserts. BMDI dust detection is shown to be limited in scenes with high atmospheric humidity as e.g. coastal regions. In particular the insensitivity of BMDI to biomass burning aerosol is shown, leading to the possibility of remote sensing of mineral dust also in regions with large contributions of biomass burning aerosol to the total column aerosol concentrations. Time series of mineral dust as inferred from BMDI for the year 2006 are presented for four regions over the Sahara. These time series show strong (and different) annual cycles of dust load for all four regions. Especially the strong episodic character of atmospheric dust in the main source regions can be inferred from BMDI observations.